2023
DOI: 10.3390/vaccines11030645
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Impact of the COVID-19 Pandemic on Routine Childhood Immunization Coverage in Cameroon

Abstract: Background: The third round of the global pulse survey demonstrated that the abrupt and rapid progression of the COVID-19 pandemic significantly disrupted childhood immunization in many countries. Although Cameroon has reported over 120,000 COVID-19 cases, the reported national childhood vaccination coverage during the pandemic seems to have increased compared to that during the pre-COVID-19 period. Indeed, the first dose of the diphtheria, tetanus, and pertussis-containing vaccine (DTP-1) coverage increased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…National coverage rates may have held steady or even increased during the pandemic, masking regions where they have fallen due to the pandemic. That happened in Cameroon, where the increase in vaccination coverage masked the impact of COVIC−19 on the vaccination of children in COVID–19 hotspot regions [ 51 ]. A study in Zimbabwe found that the prevalence of missed opportunities for vaccination was 9% among mothers with no education and 21% among educated mothers.…”
Section: Discussionmentioning
confidence: 99%
“…National coverage rates may have held steady or even increased during the pandemic, masking regions where they have fallen due to the pandemic. That happened in Cameroon, where the increase in vaccination coverage masked the impact of COVIC−19 on the vaccination of children in COVID–19 hotspot regions [ 51 ]. A study in Zimbabwe found that the prevalence of missed opportunities for vaccination was 9% among mothers with no education and 21% among educated mothers.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has substantially disrupted routine immunization services in the World Health Organization (WHO) African Region, leading to precipitous decline in childhood vaccination rates compared to pre-pandemic levels [1][2][3][4]. The African region is one of the six regions of the WHO and is made up of 47 out the 54 countries of the African continent [5].…”
Section: Introductionmentioning
confidence: 99%
“…The Special Issue features research, reviews, and commentaries that span a range of immunization topics and populations. While there is an emphasis on childhood vaccinations [ 15 , 16 , 17 , 18 ]—exploring inequalities in DTP and measles-containing vaccine (MCV) coverage [ 19 , 20 , 21 , 22 , 23 ] and patterns of inequality in unvaccinated or zero-dose children [ 24 , 25 , 26 , 27 , 28 , 29 ]—contributions also cover inequalities in adult immunization [ 30 ], including protection of pregnant women and their newborns against tetanus [ 31 ] and COVID-19 vaccination [ 32 , 33 ].…”
Section: The Special Issue: Monitoring Inequalities and Understanding...mentioning
confidence: 99%
“…An encouraging observation while putting together this Special Issue has been the use of a variety of data sources to assess immunization inequalities. Studies have made use of traditional sources of immunization data like administrative data [ 19 , 23 , 32 ] and population surveys [ 18 , 21 , 22 , 27 , 29 , 30 ] (including Demographic and Health Surveys and/or Multiple Indicator Cluster Surveys [ 15 , 20 , 31 ]), while several other studies explored the potential of novel sources such as geospatial data [ 24 , 25 ], electronic immunization registries [ 34 ], dialogues [ 16 ], country appraisals and reports [ 35 ], and funding proposals [ 26 ]. Three review studies relied on synthesis and structured analyses drawing from a multitude of existing studies [ 17 , 33 , 36 ].…”
Section: The Special Issue: Monitoring Inequalities and Understanding...mentioning
confidence: 99%